Exploring Canadian Integration through Critical Discourse Analysis of English Language Lesson Plans for Immigrant Learners - Barker, Marianne Elaine (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
The Canadian government implemented the Language Instruction for Newcomers to Canada (LINC) program to help immigrants integrate into Canada. However, research indicates that the LINC program fails to achieve its integrative goals. Using Fairclough’s analytical concepts of genre, discourse and style, this article closely examines a unit of LINC lesson plans to understand how they advance an understanding integration among classroom stakeholders (Canadian teachers and immigrant students). The analysis reveals that the LINC curriculum proliferates inequality between Canadians and newcomers by fostering an assimilative orientation that subjugates immigrants as problematic Others. Immigrants are expected to conform to dominant Canadian ways of being and ways using language. This article calls for a rethinking of integration by identifying possibilities for resistance that could shift immigrants’ positioning and reduce discrimination. This could occur through better recognizing bias and dominance, and through acknowledging and validating newcomers’ ways of speaking and interacting.